2019
DOI: 10.1016/j.tmrv.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Complement in Transfusion-Related Acute Lung Injury

Abstract: a b s t r a c tTransfusion-related acute lung injury (TRALI) is a life-threatening complication of acute respiratory distress occurring within 6 hours of blood transfusion. TRALI is one of the leading causes of transfusion-related fatalities and specific therapies are unavailable. Neutrophils are recognized as the major pathogenic cells, whereas T regulatory cells and dendritic cells appear to be important for protection against TRALI. The pathogenesis, however, is complex and incompletely understood. It is fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 84 publications
0
20
0
3
Order By: Relevance
“…Although several studies have reported that a PRBC transfusion can negatively affect clinical outcomes [46,47], it still remains unclear if TAFI is an acute phase reactant that links hemostasis and inflammation or whether it plays an active role in the development of post-traumatic sepsis. With regard to the effects of PRBC transfusions on, e.g., the complement, certain clinical syndromes such as transfusion-related acute lung injury (TRALI) and transfusion-associated circulatory overload (TACO) that occur within 6 h of blood transfusions indicate an association [48,49]. The major drivers of those complications and their pathogenesis, however, are complex and incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported that a PRBC transfusion can negatively affect clinical outcomes [46,47], it still remains unclear if TAFI is an acute phase reactant that links hemostasis and inflammation or whether it plays an active role in the development of post-traumatic sepsis. With regard to the effects of PRBC transfusions on, e.g., the complement, certain clinical syndromes such as transfusion-related acute lung injury (TRALI) and transfusion-associated circulatory overload (TACO) that occur within 6 h of blood transfusions indicate an association [48,49]. The major drivers of those complications and their pathogenesis, however, are complex and incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…The antibodies from transfused blood components bind to the pulmonary endothelium followed by accumulation and activation of neutrophils. Activated neutrophils undergo respiratory burst and release ROS, release proteolytic enzymes by degranulation, and form NETs, which further contribute to lung inflammation [ 24 ].…”
Section: Overview Of Lung Inflammatory Injurymentioning
confidence: 99%
“…Bioactive lipids, formed during storage, have also been investigated for their ability to promote TRALI, yielding contradicting results [168,171], further suggesting a role for factors related to donor specificity [172][173][174]. The complement system [175], gut microbiota [176], and other soluble factors, such as osteopontin [177], have also been suggested to play a role in neutrophil accumulation and capillary leakage leading to TRALI. Of note, certain clinical subsets of TRALI do not implicate neutrophils as the key pathogenic cell subset as illustrated by the occurrence of TRALI in neutropenic patients [178,179] and in neutrophil-depleted animal models [180].…”
Section: Transfusion-related Acute Lung Injury (Trali)mentioning
confidence: 99%